Reading Signs On The Tiwah Ritual Of Kaharingan Adherent In Central Kalimantan: Semiotic Perspective Of Roland Barthes - Imam Qalyubi; Misrita Misrita (CV. Syntax Corporation Indonesia, 2023)
This paper reviews the signs or symbols on the Tiwah ritual of the Kaharingan adherent in the Central Kalimantan region, using a concept whis was initiated by Roland Barthes. The analytical model offered by Barthes is E - R - C. In the Tiwah ritual there are a variety of signs and interesting and useful significance if studied. From the results of the discussion was found that meaning of sign on Tiwah ritual was not single and final. From the results of the analysis using the E-R-C model, in Tiwah rituals found such as the connotative meaning of tanteluh or chicken eggs Ngaju Dayak language it means sacred and serves as an antidote to evil, while when compared to Javanese example eggs are interpreted as symbol of human origin or sangkan paraning dumadi. From this two findigs shows that meaning was dynamic.